Pushover analysis for seven Storey building in an earthquake risk area - Masrilayanti, Masrilayanti; Wahyuni, Nur; Amrina, Elita; Adji, Bayu Martanto (Akademisi dan Saintis Indonesia (ASASI), 2024)
West Sumatra Province, especially Padang City, is one of the earthquake-prone areas because it is located on the west coast of Sumatra, which is tectonically close to the subduction zone, namely the meeting zone or boundary between two tectonic plates where the movement of these two plates results in a large earthquake. As an area that is prone to earthquakes, knowledge about earthquake-resistant structures is very important. One method that is commonly used today is to carry out analysis to obtain the performance level of the structure. A 7-story government building located in an earthquake-prone area will be the object of this research. The building is made of concrete material, with a frame concept and is used for public purposes, so this structure's level of importance is high. This study examines the condition of a government building's resistance to seismic behavior. The method used is to look at the structural behavior of the 7-story building with pushover analysis. The pushover method is one method of the performance-based design concept. With the ATC-4o standard as a reference, the building is analyzed using the pushover method to understand its seismic behaviour. The results obtained indicate that the building is experiencing immediate occupancy conditions.